Nanomedicine: A great boon for cardiac regenerative medicine - Choudhury P.; Kandula N.; Kosuru R.; Adena S.K.R. (My University, 2025)
Cardiovascular disease (CVD) represents a significant global health challenge, remaining the leading cause of illness and mortality worldwide. The adult heart's limited regenerative capacity poses a major obstacle in repairing extensive damage caused by conditions like myocardial infarction. In response to these challenges, nanomedicine has emerged as a promising field aimed at improving treatment outcomes through innovative drug delivery strategies. Nanocarriers, such as nanoparticles (NPs), offer a revolutionary approach by facilitating targeted delivery of therapeutic agents directly to the heart. This precise delivery system holds immense potential for treating various cardiac conditions by addressing underlying mechanisms such as inflammation, oxidative stress, cell death, extracellular matrix remodeling, prosurvival signaling, and angiogenic pathways associated with ischemia-reperfusion injury. In this review, we provide a concise summary of the fundamental mechanisms involved in cardiac remodeling and regeneration. We explore how nanoparticle-based drug delivery systems can effectively target the afore-mentioned mechanisms. Furthermore, we discuss clinical trials that have utilized nanoparticle-based drug delivery systems specifically designed for cardiac applications. These trials demonstrate the potential of nanomedicine in clinical settings, paving the way for future advancements in cardiac therapeutics through precise and efficient drug delivery. Overall, nanomedicine holds promise in revolutionizing the treatment landscape of cardiovascular diseases by offering targeted and effective therapeutic strategies that address the complex pathophysiology of cardiac injuries. © 2024 Elsevier B.V.